CORPORATE SOCIAL RESPONSIBILITY PT. RIAU ANDALAN PULP AND PAPER DI KELURAHAN TELUK MERANTI KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN TAHUN 2015-2016 - Rayun Ramadhan; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine the relationship society, government, and private in preparation corporate social responsibility PT. RAPP programs in Teluk Meranti village. The problem in this research is corporate social responsibility activity implemented by PT. RAPP is almost the same in every year and more inclined to charity. This can be seen in corporate social rensponsibility program activities 2015-2016. Therefore, the problem formulation this research is how relationship society, government, and private in preparation corporate social responsibility programs. With the aim to know and analyze stakeholders relationship in preparation corporate social responsibility programs. This research uses qualitative research method with descriptive research type with data collection is done by observation, interview, and documentations. From the results of the research show that relationship society, government, and private in preparation corporate social responsibility carry out their repective dutie. This is seen when implementation rembuk desa. Rembuk desa implemented request by PT. RAPP. At the time rembuk desa, public expressed his aspiration to be recorded by company, then company discussed it further in company office. While the role of the company is more dominant in determining all activities to be implemented. The company also performs several stages in preparation. First, make evolution as an benchmark of future activities. Second, the company follows government’s musrenbang. And lastly do activity assessment.Keywords: Relationship society, government, private, Corporate Social Responsibility